Relationship between sensory organization testing scores with lower extremity injuries and prior concussion in professional soccer players - Mooney, J.; Cochrane, G. D.; Gould, S. (Clinical Journal of Sport Medicine, 2023)
Objective: To evaluate for associations between concussion history or lower extremity (LE) injury and computerized sensory organization testing (SOT) performance in professional soccer players.